Pengaruh Anemia dan Preeklampsia terhadap Kejadian Bayi Berat Lahir Rendah (BBLR) - Cahyani, Pramesty Regita; Dahliah, Dahliah; Makmun, Armanto; Kamaluddin, Irna Diyana Kartika; Darma, Sidrah (Wal'afiat Hospital Journal, 2024)
Anemia and preeclampsia during pregnancy contribute significantly to the risk of low birth weight (LBW) in neonates. Anemia, characterized by hemoglobin levels below 11 g/dL in the first and third trimesters, and below 10 g/dL in the second trimester, and preeclampsia, which involves hypertension and organ dysfunction after 20 weeks of pregnancy, can interfere with the supply of oxygen and nutrients to the fetus, causing LBW. The study conducted a Literature Review of 840 articles, and found that anemia increased the risk of LBW by about 1.49 times, while preeclampsia also had a significant association with LBW. These findings suggest the importance of early detection and treatment of anemia and preeclampsia to improve neonatal health outcomes. Further research is needed to develop more effective interventions to address these conditions.